2020
DOI: 10.1039/d0na00315h
|View full text |Cite
|
Sign up to set email alerts
|

Reversible changes in the orientation of gold nanorod arrays on polymer brushes

Abstract: Gold nanorod (GNR) arrays were prepared by GNR attachment on anionic polymer brushes via electrostatic interactions and their orientation reversibly changed by the modulation of interactions between GNRs and polymers via changes in the solution pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…This result supports the notion that the mechanism underlying the orientational change differs from our previously established system of pH-triggered orientational tuning, which relies on the electrostatic interaction strength between DNA and cationic AuNRs. [41] Whereas the interaction strength is indeed an important factor for the AuNR orientation, as we have previously reported, [39] decreases in the interaction strength by increases in pH (from the initial strength to the strength at AuNR detachment) did not induce the AuNR orientation change until AuNR detachment (Figure S7, Supporting Information). Furthermore, dynamic orientation change did not occur in double-stranded DNA (dsDNA) brushes, which are more rigid than ssDNA brushes (persistence length: ≈50 nm for dsDNA, [51] 2-3 nm for ssDNA [52,53] ) (Figure S8, Supporting Information).…”
Section: Dynamic Orientation Change Of Aunrs In the Dna Brushes With ...supporting
confidence: 58%
See 1 more Smart Citation
“…This result supports the notion that the mechanism underlying the orientational change differs from our previously established system of pH-triggered orientational tuning, which relies on the electrostatic interaction strength between DNA and cationic AuNRs. [41] Whereas the interaction strength is indeed an important factor for the AuNR orientation, as we have previously reported, [39] decreases in the interaction strength by increases in pH (from the initial strength to the strength at AuNR detachment) did not induce the AuNR orientation change until AuNR detachment (Figure S7, Supporting Information). Furthermore, dynamic orientation change did not occur in double-stranded DNA (dsDNA) brushes, which are more rigid than ssDNA brushes (persistence length: ≈50 nm for dsDNA, [51] 2-3 nm for ssDNA [52,53] ) (Figure S8, Supporting Information).…”
Section: Dynamic Orientation Change Of Aunrs In the Dna Brushes With ...supporting
confidence: 58%
“…Single-stranded DNA (ssDNA) brushes were fabricated following our previously established method with slight modifications. [39][40][41] Briefly, biotinylated ss-DNA was immobilized on streptavidin-immobilized substrates through avidin-biotin interactions. To achieve varied thicknesses, six ssDNA lengths (50,100,125,148,175, and 200 bases) were selected for each ssDNA brush.…”
Section: Aunr Orientation In Dna Brushes With Various Thicknessmentioning
confidence: 99%
“…3(a) and (b), respectively. The literature survey 30,34 revealed that the hydrogen bonding of the lone pair of N-atoms of the lactam ring in PVCL plays a vital role in the stretching frequency of the amide I band of PVCL. The stretching frequency originating at 1610 cm −1 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of AuNRs leads to a red shift in the emission wavelength of the ANS-PVCL aqueous system, making the coil conformation of the polymer more stable up to higher concentrations. survey 30,34 revealed that the hydrogen bonding of the lone pair of N-atoms of the lactam ring in PVCL plays a vital role in the stretching frequency of the amide I band of PVCL. The stretching frequency originating at 1610 cm À1 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the past few years, surface-enhanced Raman scattering (SERS) has gained increasing popularity in authentication, , detections, , and diagnostics. , Apart from its high sensitivity, SERS possesses intrinsic advantages in comparison with other spectral techniques, including highly resolved spectral bands, alleviated photobleaching, as well as operation over a wide range of excitation wavelengths. These essential features suggest the capability of SERS fingerprint in barcoding and anticounterfeiting applications. As an optical technique that depends on electromagnetic field enhancement from plasmonic nanostructures, preparation of plasmonic nanostructures becomes an indispensable step toward those emerging applications. , Although tremendous efforts have been devoted to fabrication of effective plasmonic substrates by self-assembly, direct wield and growth of plasmonic building blocks as secondary structural domains suggests a straightforward route to plasmonic nanostructures bearing intense built-in hotspots. , However, this pathway has proved to be very difficult to achieve because nanocrystal growth principally yields symmetrical nanocrystals with simple morphologies due to thermodynamic preference. Furthermore and importantly, single hierarchical nanostructures that eradicate fluctuation of nanoparticle spacing may afford a steadier enhancement for Raman scattering. Therefore, the development of a growth pathway to plasmonic hierarchical nanostructures are in high demand from both fundamental and technological aspects.…”
Section: Introductionmentioning
confidence: 99%